Effect of cypermethrin on the control of lesser mealworm (Alphitobius diaperinus) and broiler performance - Souza, Christian J.D.; Barbosa, Fabiele M.O.; Puzotti Marujo, Maíra M. [UNESP]; Santos, Elaine Talita [UNESP]; Domingues, Carla H.F.; Oliveira, Daiana; Sgavioli, Sarah (FapUNIFESP (SciELO), 2021)
This study analysed the effectiveness of using different levels of a product based on 6% cypermethrin and 2% citronella on broiler production and control the lesser mealworm (Alphitobius diaperinus). A total of 648 one-day-old chicks (Cobb®) which were allocated to one of three treatments (no application of the commercial product - control, and two concentrations of the product 2.00 and 3.33g/m2) in eight replicates with 27 birds each. The commercial product, which was based on cypermethrin was applied in the chambers with an atomizer. The lesser mealworm population was sampled weekly (1, 7, 14, 21, 28, 35 and 42 days of the experiment) using traps, at three points (front, middle and back) inside the pen. The performance, carcass and cut yields were evaluated. At 21, 28, 35 and 42 days of the experiment, the number of lesser mealworm adults and larvae was lower in the treatment groups involving 2.00 and 3.33g/m2 of the product than in the control group. On the first and 14th days of the study, the number of lesser mealworms adults was lower in the group treated with 3.33g/m2 of the product compared to the control group, although the results did not differ statistically from those obtained with 2.00g/m2 of the product. In conclusion, the application of the commercial product at both concentrations (2.00 and 3.33g/m2) was effective in combating Alphitobius diaperinus adults and larvae, and the performance was not influenced by treatments.
Keywords: Alphitobius diaperinus; Animal production; Broiler performance; Cypermethrin; Insecticide; Lesser mealworm; Pest control